HUBUNGAN PENGETAHUAN TENTANG KODE ETIK KEDOKTERAN INDONESIA DENGAN SIKAP DOKTER TERHADAP PENGGUNAAN MEDIA SOSIAL DI JAKARTA SELATAN TAHUN 2022 - Fallery Setyaprawira Wibisono (2023)
Social media is an online platform that people use to establish social connections with others who have similar jobs, passions, hobbies, backgrounds, and real-world ties. The daily use of social networking is increasing, particularly among Indonesian doctors. Every aspect of an Indonesian doctor's life is governed by the country's Code of Medical Ethics. The Indonesian Code of Medical Ethics is a published internal professional code of ethics. Though some dishonest medical professionals, including doctors, are suspected to be misusing social media, they nonetheless violate ethical rules. In order to compare doctors' views on social media usage to those of the Indonesian Code of Medical Ethics, this study compares doctors' opinions. The investigation in this study is cross-sectional and analytical in nature. The sample was created using a simple random sampling method and consisted of 94 respondents. The majority of responders were female and between the ages of 25 and 34, according to a univariate analysis. Only a small fraction of all respondents had excellent knowledge and positive attitudes toward using social media. The Chi-square test study revealed no statistically significant association between doctors' opinions on social media use and their comprehension of the Indonesian Code of Medical Ethics (p = 0.173). The results of this study show that there are numerous additional factors, such as culture, social norms, environment, and religion, that affect attitudes in addition to knowledge of the Indonesian Medical Code of Ethics.